Persistent cutaneous lesion in a child with tyrosinemia: Esomeprazole‐induced lichenoid drug eruptions - Bahareh Abtahi‐Naeini; Hossein Saneian; Shakiba Dehghani (Clinical Case Reports, 2021)
Abstract Lichenoid drug eruptions (LDEs) are among well‐recognized adverse reactions that different drugs including Proton‐pump inhibitors (PPIs) are associated with. LDEs are rare adverse reaction of PPIs but they should be considered as appropriate management can lead to full resolution. Herein, we report a case of Esomeprazole‐induced LDE in a child with tyrosinemia.